Community Empowerment Through the Digitalization of Nagari Administrative Services in Tanah Datar Regency - Ana Zahara; Eka Chyntia; Muhaddis Muhaddis (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to examine how the digitalization of Nagari administrative services can empower communities in Tanah Datar Regency. Using a case study method, the study finds that the digitalization of Nagari administrative services can improve the efficiency and effectiveness of public services, enabling communities to access services more easily and quickly. In addition, digitalization can enhance the transparency and accountability of Nagari governance. The study also finds that the implementation of e-government through online applications can improve the quality of public services in Tanah Datar Regency. Thus, the digitalization of Nagari administrative services can be a strategy to empower communities and enhance the quality of public services. However, the study also highlights several challenges in implementing the digitalization of Nagari administrative services, such as limitations in information and communication technology infrastructure and the insufficient capability of human resources in using digital technology. Therefore, training and support are required to enhance the capacity of human resources in utilizing digital technology.